On K. Mahler’s conjecture on the measure of the set of S-numbers - Sprindzuk, V. G. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Г. Спринджук. К гипотезе К. Малера о мере множества S-чисел V. Sprindžiuk. K. Malerio hipotezės apie S-skaičių aibės matą